Volcanic structure and composition of Old Shiveluch volcano, Kamchatka - Gorbach Natalia; Portnyagin Maxim; Tembrel Igor (My University, 2013)
This paper reports results of a new comprehensive geological mapping of the Late Pleistocene Old Shiveluch volcano. The mapping results and geochemical data on major and trace element composition of the volcanic rocks are used to characterize spatial distribution, eruptive sequence and volumetric relationships between different rock types of the volcano. Old Shiveluch volcano had been constructed during two main stages: initial explosive and subsequent effusive ones. Pyroclastic deposits of the initial stage are represented by agglomerate and psephytic tuffs with very few lava flows and form at least 60% of volume of the Old Shiveluch edifice. The deposits of the second stage are dominantly lava flows erupted from four vents: Central, Western, Baidarny and Southern, reconstructed from the field relationships of their lava flows. About 75% of the Old Shiveluch edifice, both pyroclastic deposits and lava, are composed of magnesian andesites (SiO2=57.3–63.8 wt.%, Mg#=0.53–0.57). The most abundant andesitic lavas were coevally erupted from the Central and Western vents in the central part of the edifice. Less voluminous high-Al basaltic andesites (SiO2=53.5–55.7 wt.%, Mg#=0.52–0.56) were produced by the Western, Baidarny and Southern vents situated in the south-western sector. Small volume high-Mg basaltic andesites (SiO2=53.9–55.0 wt.%, Mg#=0.59–0.64) occur in the upper part of the pyroclastic deposits.
Keywords: 38.37.19 Магматизм и магматические горные породы; 38.37.25 Вулканология; Шивелуч; Kamchatka